A distributed model of collective creativity in free play - Kalaydjian, Juliette; Laroche, Julien; Noy, Lior; Bachrach, Asaf (Frontiers in Education, 2022)
A group of children engaged in collective free play can spontaneously create new rules, learn to follow them, or find opportunities to break established ones. This rule-playing can be considered as a specific manifestation of the more general phenomenon of collective creativity. In behavioral sciences, collective creativity is often discussed as a collection of individuals each being creative. An alternative perspective views collective creativity as a distributed phenomenon: collective creativity is not a property of individual agents but rather, it emerges from the interactions within a group. Approaching free play as a case of distributed collective creativity, we understand rule-playing in terms of two complementary modes – group exploration and group exploitation-, and the transition between them. Free play is not easily amenable to fine-grained observational analysis. To overcome this, we developed the Grid Game, a new experimental setup which supports detailed empirical investigation while preserving the essence of free play. The Grid Game is a group improvisation game that uses the turn taking logic and spatial organization of typical board games, without any other predefined rules. Small groups of kids (4–5 participants) took turns in freely moving or manipulating a provided set of objects on a large 4 × 4 grid on the floor for 10 min, while being video-recorded. Despite the absence of predefined goals, simple proto-games with ad hoc rules often emerge, for example, placing objects on top of each other (create a tower) or an aiming-to-a-target shooting game. We propose an analysis of the emergence of such proto-games in terms of group exploration and exploitation. Building on our previous work on the Creative Foraging Game, we focus on cases of transition from exploration to exploitation underlying the discovery of a new form or rule. Based on Choreographer João Fiadeiro’s body of work, we describe these phase shifts as a distributed process composed of three stages: (1) Suggestion, (2) Recognition, and (3) Confirmation. We provide detailed descriptions of game moments according to this model which demonstrate the distributed nature of collective creativity in free play.